5 - An Investigation into the Effectiveness of the University Curriculum in Preparing Pre-service Technology Teachers - Mji, Andile (Journal of Higher Education in Africa, 2022)
The purpose of this study is to investigate the effectiveness of the univer- sity curriculum in preparing pre-service technology teachers. The study examines the course guide of the technology education course at one of the universities of technology in South Africa in relation to grades 7–9 (senior phase) of the technology policy document. The study found that the university technology curriculum places emphasis on both content breadth (CB) and content strands (CS). However, some of the CSs in the university technology curriculum have no relevance to the CB and were not designed to enhance its depth. Therefore, this means that the CSs of the university technology curriculum were not designed to focus on the notion of ‘fitness- for-purpose’ which is market driven. However, it is imperative that students be given an opportunity to explore both CB and content depth (CD) as well as how other CSs can be used to develop a deeper understanding of CB.